INFORMATION TECHNOLOGY OF PROCESSING ROW CROPS. RADIOMETRIC ASPECTS - Morschavka, S. V.; Pisa, D. M.; Belousov, E. L. (Radio Electronics, Computer Science, Control, 2024)
Proving ground experimental studies of high resolution spectral characteristics of plants have been conducted. Appropriate algorithm of recognition has been successfully selected. It has been shown that the proposed method of discriminatory analysis allows to achieve average probability of proper classification exceeding 80 %. The results show that intellectual technologies can be basically used in agricultural production.